2007
DOI: 10.1111/j.1551-2916.2007.01625.x
|View full text |Cite
|
Sign up to set email alerts
|

Diamond Growth on a Si Substrate With Ceramic Interlayers

Abstract: Deposition of diamond films on Si substrates precoated with a series of ceramic intermediate layers was examined. The interlayers containing SiC, SiNx, SiCN, TiSiN, and TiAlSiN were prepared by a liquid injection plasma‐enhanced chemical vapor deposition (PECVD) method using alkoxide solution precursors. The subsequent diamond synthesis on these coatings was carried out by microwave plasma‐assisted CVD (MPCVD) using a H2–1%CH4 mixture. A higher nucleation density of diamond was obtained on these intermediate l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…Meanwhile, the peak was broad, which arose from the fact that some grains on coating reduced their grain size to nanoscale. As the characteristic peak of carbon structure in small size, the weak Raman peak in the vicinity of 1143 cm-1 can be characterized as nano diamond coating [4]. The Raman characteristic peak of graphite at 1534 cm-1 indicated that there still were non-diamond compositions on coating.…”
Section: Experimental Results and Analysismentioning
confidence: 99%
“…Meanwhile, the peak was broad, which arose from the fact that some grains on coating reduced their grain size to nanoscale. As the characteristic peak of carbon structure in small size, the weak Raman peak in the vicinity of 1143 cm-1 can be characterized as nano diamond coating [4]. The Raman characteristic peak of graphite at 1534 cm-1 indicated that there still were non-diamond compositions on coating.…”
Section: Experimental Results and Analysismentioning
confidence: 99%
“…These studies demonstrate that the nucleation density, growth rate, structure orientation, and adhesion ability of diamond films are influenced by many complex factors, including the reactor types, deposition parameters, surface conditions, and chemical compositions of the substrates to be coated. [5][6][7][8] In particular, it has been widely observed that the growth of high quality diamond on bulk transition metals such as Fe, Co, Ni, and their alloys is difficult primarily due to the initial formation of a graphite intermediate layer on the substrate surfaces. [9][10][11] Nevertheless, a very thin interlayer of such transition metals coated on Si has been found to effectively enhance diamond nucleation.…”
Section: Introductionmentioning
confidence: 99%